Drug-triggered self-assembly of linear polymer into nanoparticles for simultaneous delivery of hydrophobic and hydrophilic drugs in breast cancer cells - Palvai, Sandeep; Anandi, Libi; Sarkar, Sujit; Augustus, Meera; Roy, Sudip; Lahiri, Mayurika; Basu, Sudipta (ACS Omega, 2017)
Breast cancer is the most devastating disease among females globally. Conventional chemotherapeutic regimen relies on the use of highly cytotoxic drugs as monotherapy and combination therapy leading to severe side effects to the patients as collateral damage. Moreover, combining hydrophobic and hydrophilic drugs create erratic biodistribution and suboptimal medicinal outcome. Hence, packaging multiple drugs of diverse mechanisms of action and biodistribution for safe delivery into tumor tissues with optimal dosages is indispensable for next-generation breast cancer therapy. To address these, in this report, we describe a unique cisplatin-triggered self-assembly of linear polymer into 3D-spherical sub 200 nm particles. These nano-particles comprise a hydrophobic (paclitaxel) and hydrophilic drug (cisplatin) simultaneously in a single particle. Molecular dynamics simulation revealed hydrophilic-hydrophilic interaction and interchain H-bonding as underlying mechanisms of self-assembly. Confocal microscopy studies evidently demonstrated that these novel nanoparticles can home into lysosomes in breast cancer cells, fragment subcellular nuclei, and prevent cell division, leading to improved breast cancer cell death compared to free drug combination. Moreover, 3D-breast tumor spheroids were reduced remarkably by the treatment of these nanoparticles within 24 h. These dual-drug-loaded self-assembled polymeric nanoparticles have prospective to be translated into a clinical strategy for breast cancer patients.